Novel therapies for graft versus host disease with a focus on cell therapies - Zeiser, Robert; Ringden, Olle; Sadeghi, Behnam; Gonen-Yaacovi, Gil; Segurado, Oscar G. (Frontiers in Immunology, 2023)
Graft versus host disease (GVHD) can occur at any period post allogeneic hematopoietic stem cell transplantation as a common clinical complication contributing to significant morbidity and mortality. Acute GVHD develops in approximately 30-50% of patients receiving transplants from matched related donors. High doses of steroids are used as first-line treatment, but are unsuccessful in around 40% of patients, resulting in the diagnosis of steroid-refractory acute GVHD. Consensus has yet to develop for the management of steroid-refractory acute GVHD, and prognosis at six months has been estimated at around 50%. Thus, it is critical to find effective treatments that increase survival of steroid-refractory acute GVHD. This article describes the currently known characteristics, pathophysiology, and treatments for GVHD, with a special focus on recent advances in cell therapies. In particular, a novel cell therapy using decidua stromal cells (DSCs) was recently shown to have promising results for acute and chronic GVHD, with improved effectiveness over previous treatments including mesenchymal stromal cells. At the Karolinska Institute, severe acute GVHD patients treated with placenta-derived DSCs supplemented with either 5% albumin or 10% AB plasma displayed a one-year survival rate of 76% and 47% respectively. Furthermore, patients with steroid-refractory acute GVHD, displayed survival rates of 73% with albumin and 31% with AB plasma-supplemented DSCs, compared to the 20% survival rate in the mesenchymal stromal cell control group. Adverse events and deaths were found to be attributed only to complications of hematopoietic stem cell transplant and GVHD, not to the study intervention. ASC Therapeutics, Inc, in collaboration with the Karolinska Institute, will soon initiate a phase 2 multicenter, open-label study to further assess the efficacy and safety of intravenous DSC treatment in sixty patients with Grade II-IV steroid-refractory acute GVHD. This novel cell therapy represents a promising treatment to combat the poor prognosis that steroid-refractory acute GVHD patients currently face.